Comparison between Penman-Monteith and Hargreaves-Samani to obtain ETo in rainy and dry years - Leitão, Erllan Tavares Costa; Souza, Michael Pratini Silva de; Farias, Josivalter Araujo de; Araujo, Ana Beatriz Alves; Bandeira, Poliana Maria da Costa; Bandeira, Priscila Pascali da Costa (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The planning and use of water in agricultural production, as well as the development of methodologies wich allow estimating the correct volume of water are essential for the establishment of efficient irrigation plans, avoiding waste in periods of water deficit. Evapotranspiration is directly related to the water consumption of plants, thus several methods were developed to determine the evapotranspiration used for this, the meteorological variables. Thus, the objective was to evaluate one of the most used methodologies, the Hargreaves-Samani method to estimate the ETo reference evapotranspiration in low and high rainfall conditions, using the Penman-Monteith method - FAO56 as reference. Automatic meteorological system, belonging to the Federal Rural University of Semi-Arid, in Mossoró, Rio Grande do Norte, was used. The data mentioned are for the period from January 2011 to December 2012. Considered to be practical, the Hargreaves-Samani model uses meteorological elements that are easily obtained, such as temperature, relative humidity and wind speed, allowing the estimation of reference evapotranspiration. It appears that the estimates from Hargreaves-Samani overestimated the ETo values when compared to the standard method in conditions of high humidity (2011), in addition to presenting significance regarding the variable wind speed, thus being able to be strongly influenced for it. We then see the need for calibration or parameterization of the Hargreaves-Samani equation's coefficients as an alternative for a better estimate, especially for cities with coastal influence.